A study to restriction the plant species of the vegetation cover on the sandy coastal strip in the western region of Libya in Zwarah, Misratah and Surt - Sharashy, Omar (Journal of Pure & Applied Sciences, 2017)
The species distribution reflects the effects of several factors at different scales. Climate, topography and soil are thought to exert influences on the plant distribution at region and landscape. Much of indigenous vegetation of Libya consists of surviving remnants of more favorable climate age. The flora of the coastal sand dune varies in accordance with the vegetational zone of Libya. Real dune plants not only tolerate burial in sand, but demand it in order to retain their vitality. the coastal sand dune vegetation in the western region of Libya are comparatively rich in the number of species. The results of the physical analysis of soil in the studied sites generally was coarse sand, the results of chemical analysis showed that, the soil content of minerals / elements there were differences between the three sites were recorded in Surt higher value in Na compared to the other two sites were 211.5 ppm while Zwarah and Misratah 153.3 and 88.67 ppm. While as Soil content of organic matter at the site of Surt was the lowest amount reached to 0.09 % compared with its Zwarah and Misratah 0.16 % and 0.25 % respectively. The results revealed that , the number of families 20 and 44 genus, and 53 species, included 26 annual herbs; 24 perennial herbs and 3 species biennial herb. The highest percentage contribution of annual herbs was recorded in the coastal sand dune habitat of Surt 46 %, while the highest percentage contribution of perennial herbs was recorded in the coastal sand dune habitat of Zwarah reached 46 %. The flora of Libya is not rich in the number of species , the landscape comprises the richest vegetation and the highest number of species known from Libya. Study of local plant species in their habitats, the aim is to know the factors and conditions that control their growth and distribution, and thus to know the composition of plant communities in these environments.